Design, implementation and modelling of the single and multiple extensor pneumatic muscle actuators. Issue 1 (1st January 2018) - Al-Ibadi, Alaa; Nefti-Meziani, Samia; Davis, Steve
ABSTRACT: The soft actuator represents a valuable addition to the robotics research area in last two decades. These actuators provide significant features such as lightweight, softness, high force to weight ratio and the ability to form in different shapes. This article presents a new length model to the single extensor pneumatic muscle actuator (PMA) which is depended on the constructed parameters and the air pressure. On the other hand, the tensile force formula of the contractor actuator has been modified to describe the extension force of the extensor PMA. The parallel structure of four extensor actuators is designed and implemented as continuum arm. The bending behaviour of the proposed arm is illustrated and modelled mathematically. The length model of the single extensor actuator has validated by the comparison between the model and the experiment data and then a neural network (NN) control system is applied to control the elongation of the extensor PMA. The kinematics for the proposed continuum arm are presented to describe the bending of the arm and its direction.